Ouro Preto, Sinfonia da metrópole: 1882-1889 - Verônica Toledo Ferreira de Carvalho (2021)
Ouro Preto, formerly called Vila Rica, is located in Brazil, more specifically in the State of Minas Gerais. The epicenter of gold exploration in the 18th century, and the first capital of the province of Minas, remained dynamic, approaching the ideals of modernity, civility and progress that were in vogue, especially during the second half of the 19th century. Through leisure, one of the most important facets for understanding the transformations of cities in Brazil, we reconstruct the fun life of Ouro Preto from 1882 to 1889, based on the records of the Liberal Mineiro newspaper. We find religious, civic and political festivities, carnival, theater, circus, bullfightings, concerts, dinners, restaurants, taverns, gambling, picnics, libraries and cafes, which moved day and night the city and distanced it from the image of a boring city disseminated by some scholars and travellers. Ouro Preto presented itself as a dynamic city. Understanding how his population spent their free time, the contradictions and peculiarities of this process, constitutes an important fragment of this history.